Unlocking Potential: The Interplay of Adjustment and Optimism in College Students - Dr. Yogita Mahadeo Khedkar (International Journal of Indian Psychȯlogy, 2025)
This study investigates the relationships between adjustment and optimism among college-going girls and boys. The transition to college, coupled with academic and social pressures, often presents unique psychological challenges that can significantly impact students’ well-being. This research aims to explore how these factors interrelate and contribute to students’ overall mental health and academic experience.